Pump drill-integrated triboelectric nanogenerator as a practical substitute for batteries of intermittently used devices. (February 2019) - Lee, Jeong-Won; Jeong, Jonghyeon; Yoo, Donghyeon; Lee, Kwangseok; Lee, Seoulmin; Kim, Dong Sung; Sim, Jae-Yoon; Hwang, Woonbong
Abstract: Numerous investigations into the application of triboelectric nanogenerators (TENGs) to daily life have been reported to date. Among the many types of TENGs, the rotation type TENG is extensively utilized because of its simple driving mechanism, high sustainability, and high energy performance. Finding an energy source and determining how to convert the energy source into rotational power are the most pertinent issues with regard to rotation type TENGs. We have developed a high performance rotation type TENG combined with a pump drill, which is one of the best inventions from ancient times. Owing to its simple structure and conversion of low-speed pumping to high-speed rotation, the pump drill has been widely used for making fire. Therefore, through the fabrication of a pump drill-integrated TENG (PDTENG), we have also successfully demonstrated the use of a PDTENG to operate measuring devices. Additionally, we have identified for the first time that the friction force increases due to electrostatic induction while the TENG is in operation, through a torque measuring experiment. This phenomenon only appears when the electrodes are connected, and electrons are flowing through the wires. The required torque for rotating the TENG shows a decreasing tendency as the rotation speed increases. This result is an important consideration, not only for rotation type TENGs, but for all sliding motion based TENGs. Graphical abstract: Highlights: A TENG combined with pump drill (PDTENG) was successfully developed. The simple PDTENG structure converts slow pumping motion into fast rotation motion. The composite energy output waveform of the PDTENG was measured and analyzed. Increase in friction force due to the electrostatic attraction was identified.